Diffraction Efficiency Enhanced Volume Holographic Gratings via Coupling Ag Thin Film - Yunping Qiu; Zhuoya Zhu; Xiaodie Wang; Xin Wang; Yongming Tang; Xiaobing Zhang (IEEE Photonics Journal, 2019)
Volume holographic gratings (VHGs) act as an in-coupler or out-coupler could be applied in holographic waveguide display system in which high diffraction efficiency is one of the key factors. Here, VHGs coupled with Ag thin film to enhance its diffraction efficiency is demonstrated. The first-order diffraction efficiency of the Ag coupled VHG increases by 34% when the uncoupled VHG is 42.8%. Numerical simulation results demonstrated that the Ag thin film could decrease the forward diffraction, corresponding with the first-order diffraction increasing in the coupled VHG. This paper provides useful information that Ag coupled VHGs may improve the diffraction efficiency of waveguide used in the head-mounted and near-eye display.